Efficacy and safety of anti-angiogenesis agents combined with chemoradiotherapy in the treatment of locally advanced cervical cancer: a meta-analysis of randomized controlled trials. Issue 2 (1st February 2023) - Zou, Yihua; Si, Yue; Tong, Fangqin; Guan, Meng; Bi, Chun; Wang, Xia
ABSTRACT: Background: Neovascularization is an important factor causing radiotherapy resistance, tumor growth, and metastasis. It may provides a new direction for treatment of cervical cancer. Objective and methods: The main objective is to systematically evaluate the clinical efficacy and safety of antiangiogenic therapy combined with CCRT in the treatment of cervical cancer. We searched major Chinese and English databases to collect relevant studies from the database establishment up to April 2022. The experimental group of the studies included used CCRT combined with anti-angiogenic therapy, while another used only CCRT. We used the ' Cochrane Collaboration's tool' to assess risk of bias and RevMan 5.4 to conduct analysis. Results: Twelve studies with 793 patients were included. Use clinical efficiency and adverse reactions as effect indicators. It showed that the combination can improve the ORR (OR = 3.52, P < 0.00001), CR(OR = 2.46, P < 0.00001), DCR (OR = 2.64, P = 0.005), and OS(HR = 0.56, P = 0.03). But it increases the risk of neutropenia (OR = 1.86, P = 0.004) and hypertension (OR = 5.57, P = 0.003). Conclusions: Combined therapy can improve the clinical efficacy of cervical cancer, but the safety needs to be considered.